2005
DOI: 10.1097/01.inf.0000178294.13954.a1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety, Immunogenicity and Efficacy of an Attenuated Rotavirus Vaccine, RIX4414

Abstract: Two doses of RIX4414 are highly efficacious, providing cross-protection (G1 and G9 strains, prevalent during this study) and early protection against any and severe rotavirus gastroenteritis and hospitalization to infants in Latin America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(172 citation statements)
references
References 41 publications
5
153
1
13
Order By: Relevance
“…This study demonstrated that in an Indian setting, two doses of RIX4414 vaccine were immunogenic: seroconversion rate of 58.3% at one month after receiving the second dose. Vaccination with RIX4414 vaccine had a mild reactogenicity profile in Indian with similar profile observed in other trials 9,10 and there were no safety concerns during the study.…”
Section: Introductionmentioning
confidence: 60%
“…This study demonstrated that in an Indian setting, two doses of RIX4414 vaccine were immunogenic: seroconversion rate of 58.3% at one month after receiving the second dose. Vaccination with RIX4414 vaccine had a mild reactogenicity profile in Indian with similar profile observed in other trials 9,10 and there were no safety concerns during the study.…”
Section: Introductionmentioning
confidence: 60%
“…RV1 vaccinederived virus has a lower ID 50 (∼10 5 PFU/mL or less) that may present a higher chance of viral transmission. 17 Transmission of rotavirus vaccine strain RV1 to unvaccinated individuals has been assessed in many studies [18][19][20][21][22][23][24][25] but only documented as occurring in 3. [18][19][20] In studies documenting RV1 transmission, seroconversion varied from 2% to 6% among placebo recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Jung soo Kim, 1 chong-Woo Bae, 2 Kyung-Yil Lee, 3 Moon sung park, 4 Young Youn choi, 5 Kwang-Nam Kim, 6 Jong Duck Kim,7 Won-soon park, 8 Jong-Beom sin, 9 ellen ai-Rhan Kim, 10 sang-Geel Lee, 11 chun soo Kim,12 sung-Ho cha, 13 Young Jin Hong, 14, * son-Moon shin, 15 Gyu-Hong shim, 16 Kyong Min choi,…”
Section: Immunogenicity Reactogenicity and Safety Of A Human Rotavirmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] A pre-licensure study was conducted in Korea to assess the immunogenicity and safety of RIX4414 vaccine. The immunogenicity results of the pre-licensure study indicated that two doses of RIX4414 were immunogenic (seroconversion rate: 66.7%) when administered to healthy Korean infants.…”
Section: Immunogenicity Reactogenicity and Safety Of A Human Rotavirmentioning
confidence: 99%